(untitled) (Journal of the College of Education for Women, 2022)
The current research aims to reveal the reality of coping the scientific research in Omani universities in the Sultanate of Oman with the requirements of the Fourth Industrial Revolution in the light of Oman’s 2040 vision. It also aims derive some suggestions to develop the scientific research in these institutions. The study has adopted a qualitative approach in which interviews were conducted. The sample consisted of (16) leaders of governmental and private higher education institutions, as well as, some experts in the field of Fourth Industrial Revolution. The theoretical significance of the study is represented by its response to Oman’s vison in 2040. It is further in line with the previous international reports and educational studies suggestions and recommendations, which accentuated the importance of higher education institutions to be ready for the fourth industrial revolution. Its practical significance is represented by its contributions in directing the authority people in the higher education institutions to improve the efforts exerted in the scientific research. Such a step helps to meet the requirements of the fourth industrial revolution and disseminate the importance of be aware of the importance of the fourth industrial revolution and meet its requirements. The study has concluded that the majority of the sample’s opinions (i.e., 69%) regarding the degree of the scientific research to cope with the fourth industrial revolution and Oman’s vision was good. On the contrary, (31%) of the opinions has considered the level of the efforts exerted by the higher education institutions on the scientific research to cope with the fourth industrial revolution limited and weak. Finally, the study has recommended adopting a number of suggested procedures that helps develop the scientific research. Such procedures are represented by shedding light on the skills and international cooperation, activating the international cooperation and community partnerships and improving the styles of teaching and learning.